Dermatitis Contact In Warehouse Workers - Agnes Ferusgel; Nur Azizah; Rosmidah Simanjuntak; Masni Masni (poltekkes kemenkes mataram, 2020)
Dermatitis contact is dermatitis (inflammation of the skin) that can occur due to work. The prevalence rate is still high among workers. Botot warehouse workers can also be at risk of experiencing this. The purpose of this study was to determine what factors influence the incidence of contact dermatitis in Botot warehouse workers in Percut Sei Tuan District, Deli Serdang Regency. Quantitative research The study population was all Botot warehouse workers, 30 workers, and all of them used as research samples. Collection by using a questionnaire with direct interviews. Data analysis using the chi-square test and multiple logistic regression. The results showed that the majority of workers during the last six months had experienced an incidence of dermatitis by 73.3%. Knowledge and personal hygiene are factors that influence the prevalence of contact dermatitis, while individual elements (age and sex) do not affect the incidence of dermatitis in Botot workers. The conclusion in this study, the most dominant factor influencing the prevalence of contact dermatitis is personal hygiene.